The effect of personality traits on the relationship between hiring decision and interviewee’s nonverbal behaviour in employment interviews - Yılmaz, Başak (My University, 2003)
İşe alım mülakatlarında, karar verenin, aday hakkında verdiği işe alım kararı üzerine etki eden değişkenlerden, adayın beden dili ve karar verenin kişilik özellikleri araştırılmıştır. Mülakat esnasında adayın kullandığı beden dili ile aday hakkında verilecek işe alım kararı arasında bir ilişki aranması amaçlanmıştır. Ayrıca benzerlik paradigmasından hareketle, adayın beden dilini kullanarak sergilediği rol ile karar verenin kişilik özelliklerinin benzeşmesinin de karar üzerinde etkili olacağı beklenmiştir. Dört gruba ayrılan deneklerden, ikisi bayan ikisi erkek olmak üzere dört yapay mülakat çekimi seyretmeleri ve bununla ile ilgili işe alım kararı vermeleri istenmiştir. Yapay mülakatların yer aldığı video çekimlerinde, adayların kullandığı beden dili ayarlanarak kendine güvensiz-içedönük ve kendine güvenen-dışadönük erkek ve bayan olmak üzere dört ayrı aday rolü yer almıştır. Baskınlık-itaatkarlık, içedönüklük-dışadönüklük, subjektiflik-objektiflik bakımından karar verenin kişilik özelliklerinin, beden dili ve işe alım kararı arasındaki ilişki üzerindeki etkisi araştırılmıştır. Araştırmanın sonucunda, mülakat esnasında adayın kullandığı beden dili bakımından, hakkında verilen karar fark yaratmıştır. Ayrıca işe alım mülakatlarında adayın cinsiyetinin de karar üzerinde etkili olduğu bulunmuştur. In this research, the effects of body language of applicants on the decision making in employment interview is investigated. The personality of the interviewer, is also thought to be a moderator variable effecting decision making, thus included to be investigated. It is aimed to find out the relationship between the body language of the candidate in employment interview and the hiring decision. Also considering similarity paradigm, it is predicted that the similarity of the role performed by the candidate using body language and the personality factors of interviewer has an influence on hiring decision. The subjects who are divided into four groups are asked to watch four records of simulated interviews of two male and two female candidates and make hiring decision for each simulation. The records of simulated interviews include four different types of candidates which are low self-confident-introverted or self-confident-extraverted, male and female, performed by manipulating the body language of the candidate. The relationship between some of the personality factors (dominance-obedience, introversion-extroversion, subjectivity-objectivity) of the interviewer, and applicants’ body language on the hiring decision is investigated. Results indicated that the body language of the applicant in the interview has an effect on the hiring decision. Also it is found out that the gender of the candidate also has an influence on hiring decision.
Keywords: Örgütsel Davranış